2006
DOI: 10.1038/sj.cdd.4401988
|View full text |Cite
|
Sign up to set email alerts
|

Role of the JNK pathway in NMDA-mediated excitotoxicity of cortical neurons

Abstract: Excitotoxic insults induce c-Jun N-terminal kinase (JNK) activation, which leads to neuronal death and contributes to many neurological conditions such as cerebral ischemia and neurodegenerative disorders. The action of JNK can be inhibited by the Dretro-inverso form of JNK inhibitor peptide (D-JNKI1), which totally prevents death induced by N-methyl-D-aspartate (NMDA) in vitro and strongly protects against different in vivo paradigms of excitotoxicity. To obtain optimal neuroprotection, it is imperative to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 33 publications
5
92
0
2
Order By: Relevance
“…JNK activation is not associated with NMDA and SKF38393-mediated neurotoxicity in STHdh Q111 cells Activation of the JNK may contribute to neuronal cell death after excitotoxicity (Brecht et al, 2005;Centeno et al, 2007). To investigate the potential role of the JNK pathway in the neurotoxic effect of NMDA and SKF38393, wild-type STHdh Q7 and mutant STHdh Q111 striatal cells were treated with 500 M NMDA or 100 M SKF38393, and the levels of total and phospho-JNK were determined by Western blot analysis.…”
Section: Receptor Activation Increases Neuronal Death In Sthdhmentioning
confidence: 99%
“…JNK activation is not associated with NMDA and SKF38393-mediated neurotoxicity in STHdh Q111 cells Activation of the JNK may contribute to neuronal cell death after excitotoxicity (Brecht et al, 2005;Centeno et al, 2007). To investigate the potential role of the JNK pathway in the neurotoxic effect of NMDA and SKF38393, wild-type STHdh Q7 and mutant STHdh Q111 striatal cells were treated with 500 M NMDA or 100 M SKF38393, and the levels of total and phospho-JNK were determined by Western blot analysis.…”
Section: Receptor Activation Increases Neuronal Death In Sthdhmentioning
confidence: 99%
“…Each gene is alternatively spliced to produce one or two variants of 46 and 54 kDa, which generates a total of at least 10 JNK isoforms with potentially different pro-survival and pro-death roles [51] . Among its pro-death roles, JNK has been shown to be important for neuronal death after excitotoxic stress because of its involvement in necrosis and apoptosis [52][53][54] . In cerebral ischemia, JNK has become an accepted target for neuroprotection because small-molecule inhibitors [55] or cell-penetrating peptides [56,57] such as D-JNKI1 (d-c-Jun N-terminal kinase 1 inhibitor), a cell-permeable peptide inhibitor of the JNK pathway, have been shown to be a powerful neuroprotective agent after focal cerebral ischemia in adult mice and young rats.…”
Section: Excitotoxicitymentioning
confidence: 99%
“…5D). Studies in non-neuronal cells have shown that JNK phosphorylation of JIP1 controls its ability to bind to AKT (Song and Lee, 2005a;Song and Lee, 2005b), whereas in cortical neurons treated with NMDA, it is reported that inhibition of JNK activity can stabilize JIP1 (Centeno et al, 2007). This suggested that glutamate stimulation induces JNK phosphorylation of JIP1 thus causing the dissociation of the JIP1-AKT complex and subsequent destabilization of the proteins in the growth cone.…”
Section: Neuronal Activity Regulates Jip1 and Akt Stabilitymentioning
confidence: 99%
“…Glutamate is the major excitatory neurotransmitter in the central nervous system and the principal neurotransmitter of cortical efferent systems (Fonnum, 1984). Previous studies have demonstrated that JIP1 can be regulated following stimulation of the N-methyl-D-aspartate (NMDA) class of glutamate receptors (Kim et al, 2002;Kennedy et al, 2007;Centeno et al, 2007). We exposed developing cultured neurons to glutamate and this led to a reduction in JIP1 protein levels that could be rescued by the NMDA receptor antagonist MK-801, but not by the AMPA/kainate antagonist CNQX (Fig.…”
Section: Neuronal Activity Regulates Jip1 and Akt Stabilitymentioning
confidence: 99%